Estratégias de financiamento do capital de giro em empresas do setor alimentício - Oliveira, Daniela Ferro de; Rocha, Flávio Dias; Lacerda, Tales Sarmento; Silveira, Victor Natanael Schwetter (Revista Gestão da Produção Operações e Sistemas, 2006)
This work aims at identifying working capital financing strategies of the food industry listed atBovespa, trying to find possible financing patterns in this industrial segment. Firstly, the article discusses therole of the financing decisions in the company management of the working capital, based on financial profilesfrom Fleuriet’s dynamic model, in addition to presenting the possible strategy options that can be adopted forthe decision-making process. Afterwards, an overview of the food industry is presented. Lastly, the authorsanalyze the financial statements of 11 companies from 2002 to 2004 in order to identify such strategies. Resultsshow the existence of more conservative financing patterns in the coffee segment and more aggressive patternsin the meat, poultry and other segments, as well as in the dairy products segment. However, there are nopatterns observed in the grain and oilseed milling segment.Keywords: Working Capital; Financing Pattern; Financial Profiles.